Transgender and The Literary Imagination Changing Gender in Twentieth-Century Writing - Carroll, Rachel (2018)
Transgender and the Literary Imagination is the first full length study to revisit twentieth century narratives and their afterlives, examining the extent to which they have reflected, shaped or transformed changing understandings of gender.